Internalisasi Pendidikan Ekonomi pada Kelompok Petani Semangka Margo Tani: Studi Kasus Pada Kelompok Petani Semangka - Ika Nur Khomariyah; Sunaryanto Sunaryanto; Cipto Wardoyo (Graduate School of Universitas Negeri Malang, 2020)
Abstract: A qualitative descriptive study was used for the process of internalizing palawija farmers to watermelon farmers in Wotgalih village, Yosowilangun sub-district, Lumajang regency. Based on the existing phenomena, the impact arising from the internalization process can be seen from the realm of economic education, especially non-formal education. Data and data sources were collected based on observations and interviews with several informants who lived in the Wotgalih Yosowilangun area. The results of the analysis of data collected from the management and members of the Margo Tani group are twofold: first, the process of internalization of palawija farmers and watermelon farmers together through three things, namely learning while working, learning by word of mouth and learning while practicing. The difference is among the three of them on palawija farmers, that is, palawija farmers' profession is obtained from generation to generation from the family. Unlike the farming of watermelons obtained through these three things without having to pay personal expenses. Second, the Impact of Internalization of Economic Education in the